2014
DOI: 10.2174/1566524013666131118114432
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Frame-Shift Mutation in PRSS1 Gene in Han Patients with Autoimmune Pancreatitis

et al.

Abstract: PRSS1: IVS 2 +56_60 del CCCAG is a noval mutant which may contribute to AIP pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Our results indicated that trypsin co-expressed with PAR2 in the pancreatic tissues neither from the patients with CALCB mutations nor that of the wild-type, it maybe supporting the effects of trypsin in the AIP. 6, 7 These findings are in agreement with previous data demonstrating that ectopic trypsinogen activation can directly stimulate the inflammation in the pancreas. 6, 7 Moreover, trypsin and tryptase acting on PAR-2 receptors, stimulate the release of neuropeptides from slices of the spinal cord (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results indicated that trypsin co-expressed with PAR2 in the pancreatic tissues neither from the patients with CALCB mutations nor that of the wild-type, it maybe supporting the effects of trypsin in the AIP. 6, 7 These findings are in agreement with previous data demonstrating that ectopic trypsinogen activation can directly stimulate the inflammation in the pancreas. 6, 7 Moreover, trypsin and tryptase acting on PAR-2 receptors, stimulate the release of neuropeptides from slices of the spinal cord (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 92%
“…4, 5 Recently, we have reported PRSS1_IVS 2+56_60 delCCCAG and PRSS1_p.Leu81Met cause ectopic trypsinogen activation resulting in AIP. 6, 7 Moreover, we have observed the perineural inflammation and anti-collagen type IV antibodies co-localized with subepithelial IgG4 deposits along the capillary walls and surrounding nerve fibers in almost all patients, 8 which highlights the involvement of neural factors in the formation of autoimmune pancreatitis.…”
mentioning
confidence: 75%
“…The genetic factors playing important roles in susceptibility to pancreatic injury are not well investigated in the AIP. Two case series have been published which disclosed that PRSS1 variants could contribute to the pathogenesis of AIP . Whether the PRSS1 and SPINK1 variants were associated with risk for AIP had not been reported before.…”
Section: Introductionmentioning
confidence: 99%
“…The A3243G transition in the MTTL1 mitochondrial gene is the most common pathogenetic mutation found in mtDNA [2,11,12,18]. This mutation is associated with a broad spectrum of clinical manifestations, including mitochondrial encephalomyopathy, lactic acidosis, stroke-like episodic syndrome (MELAS) and maternally inherited diabetes and deafness syndrome (MIDD) [4,8,15,21].…”
Section: Discussionmentioning
confidence: 99%
“…Three genes involved in pancreatitis -PRSS1, SPINK1, and CFTR -were sequenced according to references [11,12,18]. The mtDNA3243 A>G and PRSS1 c.410 C>T mutations (p.Thr 137 Met) were examined by polymerase chain reaction (PCR) and direct sequencing.…”
Section: Dna Extraction and Molecular Genetic Analysismentioning
confidence: 99%